Effectiveness of Oral Speech Corpora in Language Teaching and Learning (On the Basis of Kazakh Speech Synthesizer) - A., Karagoishiyeva D.; A., Ospankulova Sh. (Farabi Journal of Social Sciences, 2019)
Abstract. The article is devoted to characterizing the first steps took in development of speech synthesizers in the Kazakh language and to defining benefits of using a speech synthesizer in the language teaching and learning process. The main aim of the article is to describe and to analyze the difficulties that developers faced in the process of inventing a speech synthesizer which produces speech in the Kazakh language. Authors try to define the notion of speech synthesizer in general and to show the stages in creating a speech synthesizer and some specific peculiarities of the Kazakh language developers should pay attention to. In addition the article gives the list of the most widespread speech synthesizers and analyzes their productivity. Keywords: Speech synthesizer, reduction, sound, diphthongoid, utterance, synchronize.